Mapping Technologies’ Impact on a Professional Program Chair’s Workload - Randy Howe (Academic Chairpersons Conference Proceedings, 2016)
Department chair practices appear more open and accountable to its publics than ever, a shift driven by want it now information demands from improved data gathering systems. In this discussion, a concept model will be presented to determine whether advanced structures and procedures live up to the hype of reducing chair workloads.
Keywords: Accountability; Organizational Change; Technology; Scholarship; Department Chair